Holman divorce paper, - Lockley, Fred, 1871-1958
In researching one of his Oregon pioneer books, Lockley came across the story of an unusual divorce of Joan and Martha Holmans in eastern Oregon in the 1840s. This is a typescript by Lockley describing an original document on the Holman divorce, but that document is not present. He talks about a man and wife, John and Martha Holman, who decided to divorce, but without a judge, there was some question as to the legality of their divorce.